2017
DOI: 10.1002/aenm.201700759
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Solving Carbon's Problems: Recent Progress of Nanostructured Carbon‐Based Catalysts for the Electrochemical Reduction of CO2

Abstract: The electrochemical reduction of CO2 to useful molecules offers an elegant technological solution to current energy security and sustainability issues because it sequesters carbon from the atmosphere, provides an energy storage solution for intermittent renewable sources, and can be used to produce fuels and industrial chemicals. Nanostructured carbon materials have been extensively used to catalyse some key electrochemical processes because of their excellent electrical conductivity, chemical stability, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
224
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(227 citation statements)
references
References 110 publications
(194 reference statements)
2
224
0
1
Order By: Relevance
“…However, as ingle catalyst showing activity in both solvent types is still rare, to the best of our knowledge.W ed eveloped ac ore-shell-structured AgNW/NC700 composite using aA gn anowire( NW) core encapsulated by aN -doped carbon (NC) shell at 700 8C. [10][11][12][13][14][15] In particular, Ag-based catalysts could selectivelyc onvertC O 2 into CO, which is widely used as syngasi nc hemical industry. Under mild conditions, up to 96 %faradaic efficiency of CO, 95 %yield of Ibuprofen and 92 %y ield of propylene carbonate could be obtained in the electrochemical CO 2 direct reduction,c arboxylation and cycloaddition,respectively,using the same AgNWs/NC700 catalyst.…”
mentioning
confidence: 99%
“…However, as ingle catalyst showing activity in both solvent types is still rare, to the best of our knowledge.W ed eveloped ac ore-shell-structured AgNW/NC700 composite using aA gn anowire( NW) core encapsulated by aN -doped carbon (NC) shell at 700 8C. [10][11][12][13][14][15] In particular, Ag-based catalysts could selectivelyc onvertC O 2 into CO, which is widely used as syngasi nc hemical industry. Under mild conditions, up to 96 %faradaic efficiency of CO, 95 %yield of Ibuprofen and 92 %y ield of propylene carbonate could be obtained in the electrochemical CO 2 direct reduction,c arboxylation and cycloaddition,respectively,using the same AgNWs/NC700 catalyst.…”
mentioning
confidence: 99%
“…

energy such as wind and solar energy has attracted enormous interest for its significant roles in mitigating CO 2 emissions and reducing dependence on petrochemicals. [3] The former involves associated multielectron transfer process and is difficult to accurately control the reaction process by external conditions, [4] while the latter is mainly due to the fact that the equilibrium potentials for most of the CO 2 RR are very close to hydrogen evolution reaction (HER) toward undesirable side-products in aqueous electrolytes, which degrades the electrocatalytic performance during the CO 2 RR process. To date, the electrocatalysts have confronted severe bottlenecks issue: poor selectivity about various accessory products in CO 2 conversion process, and loss of efficiency toward competing hydrogen evolution.

…”
mentioning
confidence: 99%
“…Thecurrent density of NSHCF900 maintained as teady value at approximately À100 mA cm À2 with no significant decay (Figure 2e), and the corresponding Faradaic efficiency of CO only decreased slightly to 93 % (Figure 2f)throughout the stability test. Fort he NSHCF900 composite,t he achievable maximum Faradaic efficiency (94 %) of CO is comparable to those of state-of-the-art electrocatalysts,r egardless of metal-based or metal-free catalysts.C ompared to those reported state-of-the-art metal-free electrocatalysts, [18,19] using relatively low catalyst loading, NSHCF900 yielded one of the highest current densities (À103 mA cm À2 ), which is one of the best metalfree electrocatalysts for electrochemical reduction of CO 2 to CO. Figure S14 shows that NSHCF900 retained well-distributed hollow nanocages within the carbonaceous nanofibers.T he EDX mappings of an individual NSHCF900 nanofiber demonstrated that C, N, and Se lements were still uniformly distributed, indicating the robust electrochemical stability and reusability of NSHCF900.…”
mentioning
confidence: 85%
“…[21] TheT afel slope of 159, 192, and 132 mV dec À1 indicated the poor kinetics on NSHCF800, NSHCF1000, and NSCF900. [18][19][20][21][22][23][24][25] In our study,N-doped hierarchically porous carbon nanofiber (NHCF900;S upporting Information, Figure S15) only yields 63 %F aradaic efficiencyfor CO in CO 2 RR, which is significantly lower than that of NSHCF900, signifying the importance of Ss pecies.T he relationship between the nitrogen and sulfur contents in catalysts and the associated CO 2 RR activity is illustrated in the Supporting Information, Figure S16, which demonstrates that pyridinic Ni st he dominant active sites for CO 2 RR, and the presence of carbon-bonded Sc an greatly enhance the catalytic activity. [20,31] We hypothesize that the doped species within NSHCF is the origin of the disparity in the catalytic activity (for example,N -doped carbons have excellent CO 2 RR capabilities).…”
mentioning
confidence: 93%
See 1 more Smart Citation